EKSISTENSI PENGADILAN PAJAK DALAM SISTEM PERADILAN DI INDONESIA - Rumadan, Ismail (Jurnal Hukum dan Peradilan, 2012)
The existence of the tax court in Indonesia as a judicial institution that is specialy expected to play a role in resolving settlement of tax disputes for those seeking justice. However, its existence has not been in line with the justice system one roof in Indonesia as mandated by the 1945 Constitution. Tax court over a regime of taxation law, not a regime of law on Judicial Power. There is not an appeal or cassation resulting tax court decision does not reflect the lack of legal certainty and a sense of justice for the people seeking justice. These conditions lead to the control of the implementation of the Tax Court is very weak. Keywords: Tax Court, Justice System, Rule of Law, Justice.